First experimental determination of the radiative-decay probability of the 31− state in 12C for estimating the triple alpha reaction rate in high temperature environments - Tsumura, M.; Kawabata, T.; Takahashi, Y.; Adachi, S.; Akimune, H.; Ashikaga, S.; Baba, T.; Fujikawa, Y.; Fujimura, H.; Fujioka, H.; Furuno, T.; Hashimoto, T.; et al. (Physics letters. B, 2021)
The triple alpha reaction is one of the most important reactions in the nuclear astrophysics. However, its reaction rate in high temperature environments at T9> 2 was still uncertain. One of the major origins of the uncertainty was that the radiative-decay probability of the 31− state in 12C was unknown. In the present work, we have determined the radiative-decay probability of the 31− state to be 1.3−1.1+1.2×10−6 by measuring the 1H(12C,12Cp) reaction for the first time, and derived the triple alpha reaction rate in high temperature environments from the measured radiative-decay probability. The present result suggests that the 31− state noticeably enhances the triple alpha reaction rate although the contribution from the 31− state had been assumed to be small.